Resolution of the African Commission on Human and Peoples’ Rights on the Protection of Sacred Natural Sites and Territories: a critical overview (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
Sacred natural sites and territories are naturally occurring areas of land or water that are held to have spiritual significance by certain communities. They form part of a broader set of cultural values or traditionalways of life for given societies or communities. With the ever-mounting pressure for economic development, industrial activities, infrastructure development and demographic changes, sacred places are on the brink ofpermanent destruction. Yet these are focal points for cultural identity and diversity as well as strong biodiversity conservation. Africa as a region, through the African Commission on Human and Peoples’ Rights, adopted Resolution 372 of 2017 to preserve and protect Sacred Natural Sites and territories (SNST). The Resolution provides for protection to be achievedthrough entrenching customary governance systems into laws to protect SNST. This article analyses the resolution and how African countries can fit such customary governance systems into current legal regimes that are remnants of a colonial epoch. The article relies on case studies of how SNST have been recognised in certain African jurisdictions such as Benin andEthiopia. It also relies on case studies of countries such as Uganda and Kenya where the author participated in promulgation of laws to protect these sites.It is the author’s argument that the Resolution is a means of achieving African cultural renaissance by advocating for recognition of African cultural rights and the revival of culture-based conservation mechanisms
Keywords: sacred natural sites and territories; earth jurisprudence; customary governance systems; rights of nature and cultural renaissance